Screening of lactobacillus strains against salmonella both isolated from Malaysian free-range chicken intestin for use as probiotic - Andri Hutari,; Waleed Shaker Jaseem,; Aidil Abdul Hamid,; Wan Mohtar Wan Yusoff, (Universiti Kebangsaan Malaysia, 2011)
A total of eight strains of Lactobacillus and two strains of Salmonella were isolated from free-range Malaysian chickens intestine. Evaluation based on in vitro studies included aggregation, co-aggregation, growth with bile salts, tolerance to acidic pH, and inhibitory activity were carried out. The isolated Lactobacillus were Lactobacillus fermentum IA, Lactobacillus fermentum IB, Lactobacillus fermentum IC, Lactobacillus fermentum ID, Lactobacillus salivarius subsp. salicinus IE, Lactobacillus salivarius subsp. salicinus IF, Lactobacillus salivarius subsp. salivarius IG, and Lactobacillus spp. IH. The corresponding isolated Salmonella were Salmonella spp. 3B21 and Salmonella spp. 1A12. The ability of aggregation and also tolerance to pH 2.5 are found in Lactobacillus fermentum ID, Lactobacillus salivarius subsp. salicinus IF, Lactobacillus salivarius subsp. salivarius IG, and Lactobacillus spp. IH. The isolate most resistance to 1% bile salts is Lactobacillus fermentum ID but observed to be weak in inhibitory activity against Salmonella spp. The best co-aggregation and strongest inhibitory activity against Salmonella spp. was observed in Lactobacillus salivarius subsp. salivarius IG. Despite being not so resistant in the presence of bile salts 0.5 and 1% (w/v), the lag time in the presence of bile salts 0.3% (w/v) of Lactobacillus salivarius subsp. salivarius IG and also for Lactobacillus spp. IH are the shortest. Based on good aggregation properties, the best co-aggregation, tolerance to acidic pH 2.5 and bile salts 0.3% (w/v) and strongest inhibitory activity against Salmonella spp., Lactobacillus salivarius subsp. salivarius IG comes out as the best candidate as probiotic for chicken.